The Web that failed - Fossato, F; Lloyd, J (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford (RISJ), 2008)
The promise of the internet is often held to be one of liberation. But how far is its reach and impact still dependent on the nature of the society in which it is being used? Based on a detailed study of three significant websites over a crucial election period, The Web that Failed argues that in Russia the hopes of 'technological liberation' have not been realised.